An exploration of the experiences and perceptions of health and allied health care students regarding interprofessional collaboration and education in a rural clinical setting in South Africa - Theunissen, Anna Luttig (Stellenbosch : Stellenbosch University, 2014)
Thesis (MCurr)--Stellenbosch University, 2014.